Ketika Parpol Mengiklankan Kandidatnya di Televisi - Haryati, Haryati (Mediator, 2007)
The use of mass media (especially television) for political campaign has started since four decades ago. US Presidential Election (1950) became an example of how advertising and news became sites of political campaign. In Indonesia, political campaign through advertising began in 1999 General Election. In effect, this phenomenon gave birth to PR Politic: the use of PR consultant to manage political campaign and political leader’s publicity. In local election of DKI Jakarta, Fortune PR and Hotline dominated campaign consultant activities for government candidates. The use of advertising and news in political campaign essentially follows marketingand promotion principles as well. Both are trying to sell products to a particular consumer by applying some strategies. Success will be measured from popularity of a particular candidate, a significant change of voter’s decision, and candidate image.